Public Opinion About The Level Of The Population Security Of The Person And Work Of Interior Omsk Region - R. V. Cherkasov; V. N. Krailo (Сибирское юридическое обозрение, 2013)
Based on of large-scale case study of public opinion conducted by the Foundation "Public Opinion" in 2012, in the article are analyzed the problems of the public opinion concerning the safety of the person and the Omsk region Interior agencies activity. Here are analyzed the factors permanently influencing the character of public valuation of the professional police activity.